Hospital-onset Gram-negative Surveillance Program annual report, 2011. - Turnidge, J.; Gottlieb, T.; Mitchell, D.; Coombs, Geoffrey; Pearson, J.; Bell, J.; Australian Group on Antimicrobial Resistance (2014)
The Australian Group on Antimicrobial Resistance performs regular period-prevalence studies to monitor changes in antimicrobial resistance in selected enteric Gram-negative pathogens. The 2011 survey focussed on hospital-onset infections, examining isolates from all specimens presumed to be causing disease. In 2011, 1,827 Escherichia coli, 537 Klebsiella species and 269 Enterobacter species were tested using a commercial automated method (Vitek 2, BioMérieux) and results were analysed using Clinical and Laboratory Standards Institute breakpoints from January 2012. Of the key resistances, non-susceptibilty to the third-generation cephalosporin, ceftriaxone, was found in 9.6% of E. coli and 9.5%-12.1% of Klebsiella spp. Non-susceptibility rates to ciprofloxacin were 10.6% for E. coli, 0.0%-8.3% for Klebsiella spp. and 0.0%-5.0% in Enterobacter spp. Resistance rates to gentamicin were 8.6%, 2.9%-10.9%, and 0.0%-15.6% for the same 3 groups respectively. Eight strains, 5 Klebsiella spp. and 3 Enterobacter spp. were shown to harbour a carbapenemase (IMP-4).